Penguatan Ekonomi Masyarakat Pinggiran Sungai Melalui Pengolahan Limbah Minyak Jelantah Menjadi Aneka Produk Ekonomid di Kota Mataram : waste cooking oil treatment - Nirmawati; Novida, Sari; Hamsyuni, Muh.; Linggarweni, Inggar (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
used cooking oil is waste from the process of friying food. in the city of Mataram there are many foods whose process is fried, so that they produce a lot of used cooking oil. the problem faced by agroindustry, households and the community in the city of Mataram is the lack of insight into processing used cooking oil that is appropriate and has economic value. so far agro-industry sells used cooking oil to thrid parties at low prices and sometimes it is used up, so that the rest is disposed of together with other waste and also used cooking oil in household. based on the problems. based on the problems faced the UNIZAR service team provides insightful solutions and training on the use of waste cooking oil into economic products and added value for the community economy. products that can be produced from used cooking oil are soapand candles. the soap produce is used to wash clothes and household furniture, while the candles are used for home lighting and or aromatheraphy candles for health. these soaps and candles can be used as souvenirs in important events. with attractive and elegant packaging, these products are able to generate income for household. marketing of souvenirs in the form of soap and candles can be done online. the output target of this activity is a nationally accredited scientific journal.